INOVASI PEMBELAJARAN DARING MENGGUNAKAN MEDIA SOSIAL PADA MAHASISWA IAIN SALATIGA - Ahmad Zakian Nurfauzan (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
This study was written to describe students' creative thinking skills in utilizing social media in learning. The subjects of this study were students of the fourth semester Islamic religious education study program which were taken by purposive sampling. The research method uses a qualitative method of digital ethnographic research strategy with data collection through observation, questionnaires, and assignment. The condition of the covid pandemic, requires learning to be done online. On the other hand, it is necessary to have online learning tools and social media as an option that can be used as media. In using social media, students can hone their creative thinking skills which include fluency, flexibility, originality, and elaboration through the resulting learning content. The results show that there is a diversity of social media used by students in learning, the use of social media in learning can be a stimulus for the development of creative thinking skills, and student responses after three semesters of online learning during the covid pandemic. With this social media-based learning, students get convenience in getting various information and fun learning makes students able to improve their creative thinking skills.